2001
DOI: 10.1016/s0008-6363(01)00209-7
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide effects on reperfusion-induced malignant arrhythmias and left ventricular mechanical recovery from stunning in conscious sheep

Abstract: Glibenclamide infusion resulted in adverse cardiovascular effects. The combined deleterious effects on reperfusion-induced arrhythmias and on myocardial recovery from stunning could be the cause of the unexplained high mortality in diabetic patients treated with sulfonylurea derivatives. The mechanism involved seems to be the blockade of the cardiac ATP sensitive potassium (K-ATP) channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…On the other hand, there are disputes about the role of K ATP in cardiac arrhythmias during an acute ischemic insult. Most of the evidence supports a scenario whereby opening of myocardial K ATP channels by hypoxia and ischemia subsequently increases potassium efflux, which leads to a shortening of the action potential duration, a depolarization of the membrane by extracellular potassium accumulation, and inhomogeneities in repolarization; this scenario creates a substrate for reentry (28)(29)(30)(31). These potentially arrhythmogenic mechanisms are implicated in the genesis of ischemic arrhythmias.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, there are disputes about the role of K ATP in cardiac arrhythmias during an acute ischemic insult. Most of the evidence supports a scenario whereby opening of myocardial K ATP channels by hypoxia and ischemia subsequently increases potassium efflux, which leads to a shortening of the action potential duration, a depolarization of the membrane by extracellular potassium accumulation, and inhomogeneities in repolarization; this scenario creates a substrate for reentry (28)(29)(30)(31). These potentially arrhythmogenic mechanisms are implicated in the genesis of ischemic arrhythmias.…”
Section: Discussionmentioning
confidence: 97%
“…Similar inhibitory effect of 10 to 100 M glibenclamide on the I Ca,L was also observed in rat aortic smooth muscle (Yoshitake et al, 1991;Bian and Hermsmeyer, 1994). Some investigators did not observe a negative inotropic effect of glibenclamide in the heart (Sykes et al, 1977;Del Valle et al, 2001). They applied glibenclamide via oral administration or intravenous injection, and the concentration of glibenclamide in plasma might be around 0.5 to 2.5 M (Del Valle et al, 2001).…”
Section: Discussionmentioning
confidence: 53%
“…Some investigators did not observe a negative inotropic effect of glibenclamide in the heart (Sykes et al, 1977;Del Valle et al, 2001). They applied glibenclamide via oral administration or intravenous injection, and the concentration of glibenclamide in plasma might be around 0.5 to 2.5 M (Del Valle et al, 2001). Our results also revealed that glibenclamide had no significant effect on contraction at concentrations Ͻ 1 M, and the threshold concentration for the effect was between 1 and 10 M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of glibenclamide on IR injury, del Valle et al reported that glibenclamide had combined proarrhythmic and cardiodepressant affects in cardiac IR injury models using sheep [32]. We could not find the reports of whether glibenclamide directly affects intestinal IR injury.…”
Section: Discussionmentioning
confidence: 62%